Sherlock. Season one [videorecording (Blu-Ray)] - Moffat, Steven, 1961-; Gatiss, Mark; Cumberbatch, Benedict, 1976-; Freeman, Martin, 1971-; Graves, Rupert, 1963- (BBC Video ; Distributed by Warner Bros. Entertainment, 2010)
A contemporary take on the classic Arthur Conan Doyle stories, Sherlock is a thrilling, funny, fast-paced adventure series set in present-day London. The iconic details from Conan Doyle's original books remain: they live at the same address, have the same names, and, somewhere out there, Moriarty is waiting for them. And so across three thrilling, scary, action-packed, and highly modern adventures, Sherlock and John navigate a maze of cryptic clues and lethal killers to get at the truth.